Hubungan Tingkatan Simtom Kecemasan dengan Self-Esteem Pelajar SMA Swasta Muhammadiyah 02 Medan - Nathasya Putri Kinanti; Nanda Sari Nuralita; Nurhasanah Nurhasanah; Des Suryani (Lembaga Pengembangan Kinerja Dosen, 2025)
Anxiety is a condition when emotions that arise when individuals are under stress, and is characterized by feelings of tension, thoughts that make individuals feel worried and accompanied by physical responses (heart beat fast, increased blood pressure, and others).1 Anxiety is related to fear and manifests as a future-oriented state of mind consisting of a complex cognitive, affective, physiological, and behavioral response system associated with preparation for anticipated events or circumstances that are considered threatening. Excessive anxiety can interfere with daily activities and be a sign of general anxiety disorder. Self-esteem is one of the main factors of how individuals see themselves or the concept of self and becomes an important determinant in human behavior. Early adolescence is the most decisive period in the formation of self-esteem which is characterized by the emergence of positive or negative self-esteem changes. Method: This type of research is analytic descriptive research with a cross sectional design. This research was conducted by looking at the relationship between the level of anxiety symptoms and self-esteem in students by giving the Beck Anxiety Inventory (BAI) and Rosenberg Self-Esteem Scale (RSES) questionnaires as research measurement tools. In this study using a sample of 90 people, where the sample was divided according to strata as many as 30 samples. Test data in this study using univariate test and bivariate test Chi-Square test. Results: the test results found that there was a relationship between the level of anxiety symptoms on the self-esteem of students of SMA Swasta Muhammadiyah 02 Medan and obtained a significant value of <0.001 (p<0.05). Conclusion: there is a significant relationship between the level of anxiety disorders to self-esteem in students of SMA Swasta Muhammadiyah 02 Medan.